Growth, yield and nutrient uptake by sesame as influenced by intercropping systems and sulphur levels under semi-arid region of Rajasthan - Shivran, A. C.; Yadav, R. K. (Annals of Agricultural Research, 2016)
An experiment was carried out at Jobner, Rajasthan during kharif season of 2011 to find out the effect of intercropping system and sulphur level in sesame. The effect of intercropping systems revealed that planting of mothbean and sesame in 2:1 paired row ratio recorded significantly higher dry matter accumulation at 60 DAS and at harvest and N, P and S concentration in seed and stover of sesame as compared to sole sesame. However, plant height at all the growth stages, dry matter accumulation at 30 DAS and oil content in seed of sesame remained statistically same as sole crop. Highest seed yield (7.21 q/ha) and total uptake of N, P and S in sesame was recorded in sole crop which significantly higher than intercropping systems. However, significantly highest sesame equivalent yield (7.90 q/ha), land equivalent ratio (1.11) and net monetary returns (Rs 24150/ha) were registered with mothbean + sesame (2:1) intercropping system. The graded levels of sulphur up to 40 kg/ha significantly increased plant height and dry matter accumulation at different growth stages, N concentration in seed and stover, P concentration and oil content in seed and total uptake of N and P, seed yield (4.46 q/ha), sesame equivalent yield (7.95 q/ha), LER (1.08) and net returns (Rs 24540/ha). However, significant improvement in P concentration in stover, S concentration in seed and stover and total S uptake were observed up to 60 kg S/ha. Thus application of 40 kg S/ha in sesame intercropping system was found suitable considering input economy as it recorded 28.62 and 8.20% higher seed yield and 42.12 and 10.93% higher net monetary returns over control and application of 20 kg S/ha, respectively.